MARIST SCHOOL INTEGRATED INFORMATION LITERACY PROGRAM (MASINFORM PROGRAM): INTEGRATION OF INFORMATION LITERACY SKILLS AND LIBRARY LESSONS IN A SCHOOL’S CURRICULUM - Evangelista-Abrigo, Dia Marie (Journal of Philippine Librarianship; Vol 38 (2018), 2018)
The paper aims to design an integrated information literacy program and to assess its effect on the information literacy skills of Marist School Grade 1-6 pupils. The research design of this study employed a mixed method approach, descriptive for the development phase and quasi-experiment for the assessment stage. The study found out that an essential factor in designing an integrated information literacy program is the strong collaboration of teachers and librarians. It also revealed that Grade 1-6 pupils information literacy skills improved after attending sessions on information literacy.
Keywords: information literacy skills, school library, integrated information literacy program